Buildings as complex systems: the impact of organisational culture on building safety. Issue 12 (2nd December 2021) - Çıdık, Mustafa Selçuk; Phillips, Stephen
Abstract: High-risk buildings can be considered as complex systems involving various social actors and technology, which draws attention to the organisational and social underpinnings of their safety. This research draws on complex systems theory and high reliability organisations (HRO) literature to develop insights into the cultural aspects of safety management and regulation of high-risk buildings. Ten semi-structured interviews were undertaken to explore the opinions and experiences of built environment professionals in England about the ongoing regulatory changes regarding high-risk buildings following the tragic fire at Grenfell Tower. The findings expose some aspects of the organisational culture that underpin the safety-related behaviour in high-risk building life cycle in England, which are incompatible with those that underpin HRO. The findings also show how the studied regulatory changes are subsumed by this organisational culture and fail to deliver their intention. Hence, the paper establishes organisational culture of the building life cycle as a key consideration for safety management and regulation of high-risk buildings. The conclusion calls for future regulatory, practical and research efforts to develop a better appreciation of the organisational culture, and to aim for measures to cultivate a culture that enables collective mindfulness.